Education debt and household consumption upgrading: Positive incentives or inhibitions? - Mianbi Xie; Xin Chen; Yingying Zhao (PLoS ONE, 2025)
Household education debt is closely related to household consumption, and education itself is also a developmental high-quality consumption. Based on the panel data of five phases of the China Household Finance Survey (CHFS) from 2013 to 2021, this paper explores the impact of households’ education debt on improving household consumption enthusiasm and consumption upgrading with households as the basic unit. The study finds that education debt can significantly promote the upgrading of household consumption. Mechanism analysis shows that education debt can promote the upgrading of household consumption by improving the level of Internet consumption, and there are different degrees of moderating effect on household risk attitude. Heterogeneity analysis shows that household education debt has a significant positive effect on the consumption of urban and rural areas, high-financially literate and middle- and low-income households, as well as middle-leveraged households. The conclusions of this study enrich the research on the influencing factors and mechanisms of household consumption upgrading, broaden the research boundary of household debt and consumption, and have important implications for promoting education equity and consumer demand in China.